Genetic diversity of Sragen Black Cattle based on D-Loop gene sequencing analysis - Rahayu Kusumaningrum; Sutopo Sutopo; Edy Kurnianto (Livestock and Animal Research, 2020)
Objective: The objective of this study was to investigate the genetic diversity of Sragen Black Cattle based on D-loop sequences analysis.Methods: A total of 25 blood samples belonged to Sragen Black Cattle that had no genetic relationship within sample. The DNA genome was extracted based on the manufacturer’s standard protocol using gSYNC DNA Mini Kit (Geneaid Biotech Ltd.). D-loop gene was amplified using specific primer forward: 5’- TAGTGCTAATACCAACGGCC-3’ and reverse: 5’- AGGCATTTTGAGTGCCTTGC-3’ and then was sequenced. The sequencing result was aligned and analyzed by Molecular Evolutionary Genetics Analysis (MEGA) version 6.0 to reveal genetic distance and phylogenetic tree. Genetic diversity and haplotype were analysed by DNA Sequence Polymorphism (DnaSp) v6.12.03.Results: The results revealed that there were 11 haplotypes with Pi = 0.00675±0.00201 and Hd = 0.767±0.086. Sragen Black Cattle was divided by two cluster in phylogenetic tree with average of genetic distance was 0.0032.Conclusions: In conclusion, all of Sragen Black Cattle are on the same cluster and have closer genetic relationship to Bos indicus rather than Bos taurus with similarity level 85.76 % based on BLAST program.